8. Woven EndoBridge system for wide-necked bifurcation aneurysms treatment: Preliminary results of the first center in Southeast Asia - An, Nguyen Huu; Luu, Vu Dang; Tuan, Tran Anh; Anh, Nguyen Quang; Kien, Le Hoang; Thien, Nguyen Tat; Trang, Nguyen Thu (Tạp chí Nghiên cứu Y học, 2023)
This study reports the initial results of wide-necked bifurcation aneurysms treated with Woven EndoBridge (WEB) system at one of the first centers in Southeast Asia from April 2019 to June 2022. A total of 12 patients (50% female, median age of 66) with 12 aneurysms (9 unruptured and 3 ruptured) were recruited. The aneurysms were located in the basilar apex (4 patients), anterior communicating artery (4 patients), middle cerebral artery (3 patients), and posterior cerebral artery (1 patient). The average aneurysm size was 6.3mm (range 4.8 - 8.0mm) with mean dome to neck ratio of 1.2 and mean neck size of 5.4 mm (range 3.7 - 6.9mm). The technique was successful in all cases (100%) without any adjunctive devices. No intraoperative rupture occurred. Thromboembolic complications that occurred in two patients resulted in death in 1 patient (accompanied by retroperitoneal bleeding) (1/12, 8.3%) and moderate disability in 1 patient (1/12, 8.3%). The MRI follow-up at 3 months showed complete occlusion in 6 aneurysms (6/11, 54.5%) and neck remnant in 5 aneurysms (5/11, 45.5%). The study demonstrated that the WEB system alone was feasible to treat both ruptured and unruptured wide-necked bifurcation aneurysms. This device seems to be a promising tool for the treatment of complex wide-necked bifurcation aneurysms.